2021
DOI: 10.31234/osf.io/vunh4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Impartial Measure of Collective Action: Development and Validation of the Belief-aligned Collective Action Scale

Abstract: Ideological bias has been a relevant issue in social psychology for the past 50 years. The investigations of collective action (CA), in particular, have mainly focused on left-oriented movements, leading to a knowledge gap on the antecedents of conservative CA. Furthermore, common measures of CA are typically characterised by two methodological limits: the inability to discriminate participants who don’t engage in CA from those who would act towards opposite goals, and unawareness whether variables included in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…The primary dependent variable of our analysis is reported intention to partake in collective action after viewing the tweets. The belief-aligned collective action scale presented in Cervone et al (2021) is used.…”
Section: Methodsmentioning
confidence: 99%
“…The primary dependent variable of our analysis is reported intention to partake in collective action after viewing the tweets. The belief-aligned collective action scale presented in Cervone et al (2021) is used.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed Belief-aligned Collective Action (henceforth, BCA) scale was developed and tested across five studies, three described here, and two available online on Open Science Framework (OSF; Cervone et al, 2022). The first two studies (reported here as Study 1a and 1b) focused on economic inequality and tested the scale on an Italian and a British sample.…”
Section: Scale Developmentmentioning
confidence: 99%
“…Given the extensiveness of socio-psychological literature on collective action (Agostini & van Zomeren, 2021) and since we wanted to develop a short measure, items for our scale were selected through a broad literature review on collective action and activism measures, giving priority to frequently used items. We also included non-normative actions (less frequently investigated in the literature) and some additional items that to our knowledge were missing from previous research (e.g., "Displaying posters or banners"; initial items and sources available on OSF; Cervone et al, 2022). The final list of items is available in Table 1.…”
Section: Item Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary dependent variable of our analysis is reported intention to partake in collective action after viewing the tweets. The belief-aligned collective action scale presented in Cervone et al ( 2021 ) is used. Examples of actions on the scale include: “ I would carry out research to learn more about possible actions I can take to promote my position” and “ I would attend a rally, a march, or a protest to assert my position.” Additionally, to make the Study 2 coherent with Study 1, we added to the scale a question on likelihood of retweeting the presented tweets.…”
Section: Study 2: Experimentsmentioning
confidence: 99%